Measuring Back Injury Risk in Mexican Workers of an Automotive Company - Cuautle, Luis (2019)
850 thousand workers per year spread across the 32 states, of which Puebla contributes with 465 106, developing, in a high percentage, the verification of new parts as part of the manufacture process. This activity is supported by the use of devices known as fixtures, whose equipment and tool forces operators to lift loads between 10 and 50 kilograms by performing manual operations to hold parts, presenting pain at the lumbar level, therefore, it is essential to measure the risks of back injuries in the study population. The objective was to identify and measure the risks of back injuries in the study population. Materials and Methods: The inspection process is analyzed by identifying the potential risk factors. Ergonomic methodologies and instruments are used, such as Quick Exposure Check (qec), the National Institute for Occupational Safety and Health (niosh) equation, the reba (Rapid Entire Body Assessment) method, Ovako’s Work Posture Analysis System (owas), among others. Results: The qec method shows that trunk/back and wrist/hand are the most sensitive parts to risk exposure, indicating that 18 % of the postures are rated 4 in the level of risk, with the back rotated and bent in over 32 % of time. The weight of the operation exceeds 20 kilograms in 71.4 %. Conclusion: Four ergonomic techniques are used to assess the risk of injury, the inspection process of manufactured parts is analyzed.